Reset : how to change what's not working - Heath, Dan, 1973- (Avid Reader Press, 2025)
"From the #1 New York Times bestselling coauthor of Made to Stick, Switch, and The Power of Moments comes a revolutionary guide to fixing what's not working-in systems and processes, organizations and companies, and even in our daily lives-by identifying leverage points and concentrating resources to achieve our goals"--